Think beyond ascites - Kalgaonkar, Prarthana; Wade, Minal; Mauskar, Anupama (International Journal of Research in Medical Sciences, 2019)
In children with gross, persistent ascites wherein clinical scenario is not agreeable to common conditions, one needs to revise the diagnosis and rule out the surgical cause for abdominal distension mimicking ascites. We are reporting here, a case of two year old female child who presented with abdominal distension, clinically suggestive of ascites and subsequently diagnosed to have a large chylous mesenteric cyst which was determined on biochemical investigations, imaging and confirmed on surgical intervention. She was managed surgically with successful outcome.